Integrating Machine Learning Models in Modern Frontend Applications - Mariappan Ayyarrappan (North American Journal of Engineering Research, 2025)
The integration of machine learning (ML) models into modern frontend applications is revolutionizing how interactive user experiences are delivered. By leveraging in-browser ML frameworks and cloud-based inference, developers can now implement functionalities such as personalized content, real-time image classification, and natural language processing directly within the client. This paper discusses architectural strategies, implementation techniques, and performance considerations for embedding ML models in frontend environments. We examine the benefits of using frameworks like TensorFlow.js and ONNX Runtime Web, detail data flow pipelines, and explore optimization approaches to overcome inherent resource constraints. Diagrams—including sequence diagrams, state diagrams, and performance bar charts—illustrate key concepts and best practices. Through AI-driven personalization and predictive analytics integrated into the browser, organizations can enhance responsiveness and user engagement while ensuring maintainability and scalability.